Patterns in the management of superficial vein thrombosis. (April 2017) - Karathanos, Christos; Spanos, Konstantinos; Lachanas, Vasileios; Athanasoulas, Athanasios; Giannoukas, Athanasios D
Objective: To highlight current practice patterns in management of superficial vein thrombosis. Methods: An electronic survey was conducted using the mailing lists of the Mediterranean League of Angiology and Vascular Surgery and European Venous Forum regarding superficial vein thrombosis diagnosis, investigation, and treatment. Results: The response rate was 41% (175/430) and the majority of the participants were vascular surgeons practicing in a hospital. More experienced physicians considered superficial vein thrombosis as a medical issue of moderate seriousness and performed duplex ultrasound for confirmation of diagnosis. Elastic stockings were recommended by 87% of the physicians, while 57% prescribed nonsteroidal anti-inflammatory drugs. Eighty six percent advised anticoagulation, although a large disparity was shown regarding regime, dose, and duration. Thrombophilia test was regularly suggested by 19% of the physicians. Ligation of the saphenofemoral junction was the treatment of choice by those who suggested intervention in the acute phase of superficial vein thrombosis. Conclusions: A great disparity exists in the management of superficial vein thrombosis. Current guidelines have not been adopted by physicians; more focused training is needed for those involved in the management of venous diseases.